Genome-wide joint SNP and CNV analysis of aortic root diameter in African Americans: the HyperGEN study - Devereux Richard B; Rao DC; Gu Charles C; Broeckel Ulrich; Meyers Kristin J; Patki Amit; Wineinger Nathan E; Arnett Donna K; Tiwari Hemant K (BMC, 2011)
Abstract Background Aortic root diameter is a clinically relevant trait due to its known relationship with the pathogenesis of aortic regurgitation and risk for aortic dissection. African Americans are an understudied population despite a particularly high burden of cardiovascular diseases. We report a genome-wide association study on aortic root diameter among African Americans enrolled in the HyperGEN study. We invoked a two-stage, mixed model procedure to jointly identify SNP allele and copy number variation effects. Results Results suggest novel genetic contributors along a large region between the CRCP and KCTD7 genes on chromosome 7 (p = 4.26 × 10-7); and the SIRPA and PDYN genes on chromosome 20 (p = 3.28 × 10-8). Conclusions The regions we discovered are candidates for future studies on cardiovascular outcomes, particularly in African Americans. The methods we employed can also provide an outline for genetic researchers interested in jointly testing SNP and CNV effects and/or applying mixed model procedures on a genome-wide scale.